Canadian-American Jurisprudence on 'Good Faith' Bargaining - Bemmels, Brian; Fisher, E. G.; Nyland, Barbara (Relations industrielles / Industrial Relations, 1986)
Until the 1970s and 1980s, the National Labor Relations Board (NLRB) enjoyed a broader remedial authority than did Canadian labor boards. US developments during those years involved delineating the NLRB's remedial authority and its exercise for bad faith bargaining. By contrast, Canadian jurisprudence on bad faith bargaining blossomed during the past decade. The British Columbia and Ontario boards were empowered to arbitrate first agreement disputes as a remedy against bad faith bargaining. The Ontario board developed such principles as preserving and maintaining the decision-making framework for negotiations and a full and free discussion. Canadian and US boards are similar in that they: 1. deal with the failure to disclose information the same, 2. have the same meaning of surface bargaining, and 3. similarly determine how concession bargaining could comply with good faith principles.
Keywords: Business And Economics--Labor And Industrial Relations; Business And Economics--Personnel Management; Collective bargaining; Good faith bargaining; Labor Unions; Labor law; Labor negotiations; Labor unions; Legislation; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z